Comparison of High-Performance Liquid Chromatography and Capillary Electrophoresis in the Screening of Haemoglobinopathies - Asghar, Shumaila; Mahmood Abbasi, Asad; Zafar, Jawad; Mahmood, Rafia; Zahir, Saima; Khan, Maria (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the results of High-Performance Liquid Chromatography and Capillary Electrophoresis in the screening of haemoglobinopathies. Study Design: Cross-sectional study. Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from May 2020 to Nov 2020. Methodology: Ninety(90) newly diagnosed patients with haemoglobinopathies were included. Patients with a history of recent blood transfusion (<4 weeks) were excluded. Venous blood samples were taken in EDTA tubes, separated into two aliquots and evaluated in parallel on High-Performance Liquid Chromatography and Capillary Electrophoresis analyzers. Results: Nine different haemoglobinopathies were encountered in the study sample. The most common condition was beta thalassaemia trait found in 50(55.6%) subjects, while Haemoglobin (Hb) (D) homozygous was the least common, detected in only 1(1.1%) subjects. A significant difference was observed between values in cases of Hb(D) Iran trait; Mean Hb(A2) percentage detected by HPLC was 41.96±1.46% compared to 1.5±0.79% detected by CE (p-value<0.001). CE detected a mean of 41.4±1.01% of Hb(D)Iran in the patients of the Hb(D) Iran trait, while High-Performance Liquid Chromatography did not detect this Hb variant (p-value<0.001). A significant difference was also found in cases of Hb(E) trait in percentages of Hb(A2) and Hb(E) variants. High-Performance Liquid Chromatography detected a mean of 31.43±2.84% of Hb(A2) compared to 4.5±0.5% detected by CE (p-value=0.003). Conclusion: Capillary electrophoresis is capable of identifying haemoglobin variants Hb(D) Iran and Hb(E) in cases of Hb(D) Iran trait and Hb(E) trait/Hb(E) homozygous, which HPLC does not pick up.